The metaphors of thought: La Potière jalouse by Claude Lévi-Strauss - Godenzzi, Juan Carlos (1986)
What can pottery, marital jealousy, and a bird that eats insects have in common? Nothing invites from first intention to establish a relationship. However, the Jívaro myths of first intention to fix a relationship. However, the Jívaro myths establish a close connection between such domains. It is that, Lévi-Strauss tells us, popular thought always manages to discover analogies and symbolic equivalences that are of the order of metaphor. In The Jealous Potter (Plon. Paris, 1985. 315 pp.), Lévi-Strauss deals with the indigenous myths of the two Americas. Through them he tries to solve three problems: One, of an ethnographic order, on the analogies of the American indigenous myths; another, concerning the logic of myths, on the common bond that is established between heterogeneous terms; and another, finally, on the relationship between mythical thought in general and meaning.